Hybrid Entrepreneurship: Combining Employment and Self Employment in Nigeria - Aladejebi, Olufemi (Archives of Business Research, 2020)
Hybrid entrepreneurship is when a person is in employment and simultaneously engaging in entrepreneurial activities. Hybrid entrepreneurship is referred to as ‘side hustle' in Nigeria. Hybrid entrepreneurship may be an option in a situation where salaried workers are not sure of retaining their employment. The theoretical framework for the study is learning and real options theory. A quantitative research technique was used for the study. Questionnaires were administered to 150 respondents using a purposive sampling method. One hundred forty-five questionnaires were valid and analysed using a 5 Likert scale. It was observed that most of the hybrid business owners were employees in the public sector; the ages of the hybrid business owners were majorly between 31 and 50. Autonomy and the need for extra income are the main reasons employees run a business alongside their work.